INTEGRASI PENDIDIKAN ISLAM KE DALAM SISTEM PENDIDIKAN NASIONAL - Riki Adi Pratama; Sunariyah, Wiwin Sunita; Zulhannan, untung sunaryo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The integration of Islamic educational values into the national education system is a crucial strategy for shaping a generation with strong character and global competitiveness. Islamic education, which is based on the principles of tawhid (monotheism), ethics, and knowledge, aligns with the goals of national education that emphasize the development of individuals who are faithful, pious, and morally upright. This article reviews the literature to analyze the contributions of Islamic education, identify implementation opportunities, and evaluate the challenges and effective integration strategies. The findings indicate that these values can be integrated through the strengthening of character education, the development of a religious school culture, and learning processes that emphasize moral and spiritual aspects. However, challenges arise, such as limited teacher competence, the lack of appropriate teaching materials, and resistance to religion-based education. Recommended strategies include enhancing teacher capacity through training, developing contextual learning materials, and fostering collaboration with stakeholders. With the right approach, Islamic education not only complements the national education system but also promotes the development of academically excellent and morally grounded generations. This article affirms the strategic role of Islamic education as a key asset in achieving the goals of national education in the era of globalization, which requires a balance between competence and moral values.